The Intention of Using Biofertilizer Among Shallot Farmers in Nganjuk Regency, East Java Province, Indonesia - Ulfa, Amelia; Burhanuddin, Burhanuddin; Purwono, Joko (Agro Bali : Agricultural Journal, 2024)
The excessive use of chemical fertilizer leads to a critical contribution to the environment, such as the decline of soil fertility and shallot productivity in the future. Whereas biofertilizer is one of the alternative ways to diminish the usage of chemical fertilizer to support sustainable agriculture. However, the majority of shallot’s farmers have a lack of knowledge towards biofertilizer. This study aims to analyze the influence of attitude, subjective norms, and perception toward the intention of using biofertilizers. This research was conducted in September 2022 – November 2022 in Gondang and Rejoso District, Nganjuk Regency, East Java, Indonesia. The respondents are considered by census method, and it is distributed to 140 shallot farmers who consist of biofertilizer users. The data was analyzed by using Partial Least Square (PLS) in order to examine the influence of attitude, subjective norms, and perception towards the intention of using biofertilizer. Overall, it is illustrated that attitude, subjective norms and perception have a positive and significant influence towards the intention of using biofertilizer among shallot farmers.